The Cooperation Between the United States and Russia in Human Spaceflights: Understanding Politics Among Human Beings in Outer Space - Berniquez-Villemaire, Nicolas (Université d'Ottawa | University of Ottawa, 2024)
American-Russian cooperation in human spaceflight constitutes a very interesting geopolitical puzzle to solve. Indeed, it may seem surprising that these two countries have managed to cooperate so extensively in human spaceflight for over 50 years through multiple projects despite the tensions and difficult geopolitical relations that these two countries maintain on Earth. While it is true that the United States and Russia cooperate in other technical areas, a deeper analysis of this puzzle is in order. The thesis therefore asks the following question: how can we explain the USRussia cooperation in human spaceflights? Building on the existing literature in the field of international relations, this thesis proposes to explore the question of human spaceflight cooperation between the United States and Russia by adopting a materialist, critical and eclectic approach. This approach uses not states, politicians or international organizations as actors and objects of study, but rather spacecraft. All the human spaceflight cooperation projects between the two countries – namely the Apollo-Soyuz Test Project (1975), the Shuttle-Mir program (1993-1998) and the International Space Station (1998-now) – are covered and for each of them, a specific spacecraft related object is studied in order to account for the whole endeavor of cooperation in human spaceflight between the two countries. To achieve this, the thesis develops a new theoretical toolbox inspired by the approaches of symbiotic realism, new materialism and science and technology studies. This toolbox, called New Space Materialism, constitutes the main thesis of this work and defends that we can understand cooperation between the United States and Russia in human spaceflights through the framework of New Space Materialism which emphasizes the role of precarity, objects and technology. The main contributions of this thesis are threefold. First, through an analysis of human spaceflight archives on a scale rarely undertaken before, this thesis improves our empirical understanding of the phenomenon of cooperation between the United States and Russia in human spaceflights. Second, there is a theoretical and conceptual contribution with the creation of the New Space Materialism theoretical toolbox that can be used to understand political issues in outer space. Finally, this thesis contributes to improve the understanding of the field of international relations in the face of cooperation between human beings in situations of scarce resources.
Keywords: International relations; Outer space; United States; Russia; New Materialism; Science and Technology; Symbiotic realism